La santé des populations de langue officielle en situation minoritaire [numéro thématique] - Leis, Anne; Bouchard, Louise (Revue canadienne de santé publique / Canadian Journal of Public Health, 2013)
Cette page éditoriale présente un numéro spécial de la Revue canadienne de santé publique qui comporte 16 articles compilant certains résultats de recherches obtenus par des chercheurs affiliés au RISF, au RRASFO et à l’Institut de recherche de l’Hôpital Montfort (IRHM), ainsi qu'un commentaire exposant les enjeux d'accès aux services de santé linguistiquement concordant au Pays de Galles.

Official language minority communities in Canada: Is linguistic minority status a determinant of mental health? - Puchala, Chassidy; Leis, Anne; Lim, Hyun; Tempier, Raymond (Canadian Journal of Public Health / Revue canadienne de santé publique, 2013)

Les inégalités sociales de santé chez les communautés francophones en situation minoritaire (CFSM) au Canada [numéro thématique] - Benoit, Monique; Bouchard, Louise; Garceau, Marie-Luce (Reflets, 2012)

Lost in policy translation: Canadian minority Francophones and health disparities - Alimezelli, Hubert Tote; Leis, Anne; Denis, Wilfrid; Karunanayake, Chandima (Canadian Public Policy, 2015)
We reviewed Canadian federal, provincial, and territorial policies related to the health of official language minorities (OLMs) and found important provincial and territorial differences as well as policies penalizing OLMs, which thus contribute significantly to health disparities and to the low vitality of OLM communities. These findings suggest the need for more aggressive, hands-on, and concerted federal and provincial/territorial government efforts to address social inequities and health disparities. Increased policy coherence between these levels of government will not only increase the health and vitality of these populations but also help close the disparity gap and lead to better health and well-being for all Canadians.

Access and use of health care services in the minority language - Gagnon-Arpin, Isabelle; Bouchard, Louise; Leis, Anne; Bélanger, Mathieu (Life within an official language minority in Canada, 2014)

Accès et utilisation des services de santé en langue minoritaire - Gagnon-Arpin, Isabelle; Bouchard, Louise; Leis, Anne; Bélanger, Mathieu (La vie dans une langue officielle minoritaire au Canada, 2014)